Pengaruh Iklan “Choi Siwon” Mie Sedaap dan Citra Merek terhadap Minat Beli Konsumen - Velice Velice; Ongky Alex Sander (Business Management Journal, 2022)
The growth of technological has a major influence in advertising agency. Advertising has the aim of introducing its products and stimulating consumer buying interest. In addition to advertising, brand image also has an important role in consumer buying interest. A positive brand image will get positive treatment and affect buying interest from the public. This study aims to examine the variables that have an influence on purchase intention, namely advertising and brand image variables. The data collected in this research is using a questionnaire in the form of a questionnaire. The results of this study are advertising and brand image have a significant and positive influence on buying interest. Of the 176 respondents obtained, this study attracted 160 respondents who were collected online via Google Form. In processing the data, this research uses SmartPls 3.0. The results of this study indicate that the Mie Sedaap Korean Spicy Chicken advertisement has its own charm because it has succeeded in conveying a clear message to consumers and every the public figures has uniqueness. Mie Sedaap has a good and quality brand image because its existence remains consistent and continues to innovate. For further research, it is expected to examine more deeply what makes the advertisement attractive and the supporting factors and also examines more deeply why Mie Sedaap can create and maintain a positive brand image.